URGENSI PEMBATASAN PERIODISASI MASA JABATAN ANGGOTA LEGISLATIF DALAM PERSPEKTIF KONFIGURASI POLITIK HUKUM INDONESIA - Yudi Junadi; Dedi Mulyadi; M. Rendi Aridhayandi; Christopher Surya Salim (Universitas Suryakancana, 2021)
Regulations regarding legislative powers contained in the 1945 Constitution of the Republic of Indonesia (1945 Constitution), but the 1945 Constitution does not clearly regulate the term of office of a legislative member, and there is no limit on the period of the legislative member's term of office as well as MD3 Law which does not contain the rules regarding limits on the legislative period of office. The problem that will be discussed in relation to legislative power in this research is: What is the background of the non-limitation period of the term of office of legislators in the parliamentary system in Indonesia? What factors are the basis for the need to limit the periodization of legislative member positions in the parliamentary system in Indonesia? What is the impact of the absence of periodic restrictions on legislative members' positions in the perspective of the legal political configuration in Indonesia? The problem approach that will be used in this study is the normative juridical approach in this study. In addition, the author studies the rule of law by examining the laws, regulations and legal concepts related to this research. Based on the results of the study it can be seen that in general that, there are no regulations governing the limitation of the periodization of the term of office of legislative members in Indonesia. The State of Indonesia is a state of law, so the government must legislate these problems to prevent abuse of power.Keywords: Legislature, Political Configuration, Periodization of Terms of Office.